2013
DOI: 10.1016/j.celrep.2013.04.022
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Wiring Diagram of the Protocerebral Bridge for Visual Information Processing in the Drosophila Brain

Abstract: How the brain perceives sensory information and generates meaningful behavior depends critically on its underlying circuitry. The protocerebral bridge (PB) is a major part of the insect central complex (CX), a premotor center that may be analogous to the human basal ganglia. Here, by deconstructing hundreds of PB single neurons and reconstructing them into a common three-dimensional framework, we have constructed a comprehensive map of PB circuits with labeled polarity and predicted directions of information f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
285
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 152 publications
(309 citation statements)
references
References 59 publications
15
285
3
Order By: Relevance
“…Outputs from this system could provide compass-like information to stabilize the direction of moving insects relative to the external celestial cue (78). This function for the CX has been described in locusts and butterflies (Danaus plexippus) but may be common across insect orders (79). Further, in S. gregaria (80), the cockroach Blaberus discoidalis (75), and Drosophila melanogaster (81,82), the CX encodes topographically organized visual information on moving objects and is capable of factoring out the confounding effects of visual motion generated by self-movement from moving objects in the environment (82).…”
Section: Consciousness In Insectsmentioning
confidence: 99%
“…Outputs from this system could provide compass-like information to stabilize the direction of moving insects relative to the external celestial cue (78). This function for the CX has been described in locusts and butterflies (Danaus plexippus) but may be common across insect orders (79). Further, in S. gregaria (80), the cockroach Blaberus discoidalis (75), and Drosophila melanogaster (81,82), the CX encodes topographically organized visual information on moving objects and is capable of factoring out the confounding effects of visual motion generated by self-movement from moving objects in the environment (82).…”
Section: Consciousness In Insectsmentioning
confidence: 99%
“…Based on Lin et al 2013 (Lin et al 2013) and Wolff et al 2015(Wolff, Iyer, andRubin 2015), who reported the anatomy of the same circuits, we were able to derive the network connections of these neurons and use them as a reference to optimize our connection estimation protocol. Lin et al 2013 (Lin et al 2013) and Wolff et al 2015(Wolff, Iyer, andRubin 2015) reported the polarity and innervated subregions of each neuron. To construct the reference connectivity of these neurons, we assumed that a neuron that projects its axonal arbor to a glomerulus forms synapses with another neuron that has its dendritic arbor in the same glomerulus.…”
Section: ∑ ܰmentioning
confidence: 99%
“…This issue was resolved by changing the parameter Th DP from 0.01 to 0.001. To validate the performance of the new classifier, we selected the 442 neurons that were reported in Lin et al 2013 (Lin et al 2013) as test neurons because their polarity has been reported in detail by two studies (Lin et al 2013;Wolff, Iyer, and Rubin 2015). We removed the EIP neuron class, which innervates the ellipsoid body, inferior dorsofrontal protocerebrum, and protocerebral bridge, because the reported polarity is inconsistent between the two studies.…”
Section: Synapse Polarity Prediction and Validationmentioning
confidence: 99%
See 2 more Smart Citations